2003
DOI: 10.1021/jf0301798
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Polyphenolic Composition of Cider Apple (Malus domestica) Fruits and Juices

Abstract: Five French cider apple varieties were compared on the basis of their detailed polyphenol profile in the cortex and in the juices. Among the factors studied, variety was the most important variability factor in fruits, whereas polyphenol profiles showed an overall stability from one year to another, and a limited decrease of polyphenol concentration was observed during the starch regression period of fruit maturation. In juices, procyanidins remained the preponderant polyphenol class with concentrations up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
152
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 29 publications
23
152
1
2
Order By: Relevance
“…As reported elsewhere [11,12], during processing of apples into juice in a conventional way the largest amount of phenolic compounds remained in the pomace and only 3-10% of the antioxidant activity present in fresh apples was found in the juice. The capacity to inhibit tyrosine nitration present in Golden Delicious and Panaia-red apple juices immediately after production was, respectively, around 18.6% and 27.8% that of the fresh fruits, this latter previously measured by Iacopini et al [37], and considerably higher than values reported by van der Sluis [29].…”
Section: Apple Juice and Pomace Antioxidant Activitysupporting
confidence: 51%
See 1 more Smart Citation
“…As reported elsewhere [11,12], during processing of apples into juice in a conventional way the largest amount of phenolic compounds remained in the pomace and only 3-10% of the antioxidant activity present in fresh apples was found in the juice. The capacity to inhibit tyrosine nitration present in Golden Delicious and Panaia-red apple juices immediately after production was, respectively, around 18.6% and 27.8% that of the fresh fruits, this latter previously measured by Iacopini et al [37], and considerably higher than values reported by van der Sluis [29].…”
Section: Apple Juice and Pomace Antioxidant Activitysupporting
confidence: 51%
“…The most popular processed apple product in the world, clear apple juice, has a lower phenolic content because, during production, only part of the compounds are extracted in the apple juice [11] and the rest remain in the pomace [12]. It was demonstrated that the consumption of cloudy apple juice may be more beneficial to human health than clear apple juice, due to its higher content of phenolic compounds and fibres [13][14][15].The loss of phenolic compounds during juice production is also due to the enzymatic oxidation of phenolics catalysed by polyphenol oxidase (PPO) in the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Along with these three some other phenolic compounds like chlorogenic acid, catechin, epicatechin and p-coumaric acid were also identified in aonla juice but their changes were not so significant during storage. Guyot et al (2003) estimated polyphenolic composition of French cider apple fruits and juices by reversed phase HPLC using UV-VIS detector. Some flavonoid and nonflavonoid phenols in Hungarian wines were identified by Bonerz et al (2008) using reversephase HPLC with a C-18 column, PDA detector and acidified water-acetonitrile as mobile phase, where detection limit for phenolics ranged from 0.1 to 1.0 mg l −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In perry processing, the use of fruit at the overripe stage is the normal practice to decrease the astringency and to increase colloidal stability during storage. Further, preliminary studies have shown that the concentration of procyanidins in the juices varied with the fruit maturity at pressing (Alberti et al, 2016;Guyot, Marnet, Sanoner, & Drilleau, 2003;Spanos & Wrolstad, 1990). Low quantities of procyanidins are found in juices compared with the initial quantities measured in fruit (Guyot et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The association between procyanidins and cell wall polysaccharides, especially pectins, can influence the transfer of procyanidins from fruit to juice (Guyot et al, 2003;Taira, Ono, & Matsumoto, 1997). The binding of condensed tannins to cell walls depends on one hand on the molecular characteristics of procyanidins, mainly their degree of polymerization but also the pyranic ring stereochemistry of the flavan-3-ols, and on the other hand on cell wall structure and composition.…”
Section: Introductionmentioning
confidence: 99%